2008
DOI: 10.1074/jbc.m802578200
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Nitric Oxide as an Endogenous Activator of the AMP-activated Protein Kinase in Vascular Endothelial Cells

Abstract: 2؉ chelator, indicating that NO-induced AMPK activation is guanylyl cyclase-mediated and calcium-dependent. Exposure of HUVECs or isolated mice aortas to either calcium ionophore A23187 or bradykinin significantly increased AMPK Thr-172 phosphorylation, which was abolished by N-nitro-L-arginine methyl ester, an inhibitor of nitric oxide synthase. Finally, A23187-or bradykinin-enhanced AMPK activation was significantly greater in aortas from wild type mice than those in the aortas of endothelial nitric oxide sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 47 publications
4
84
1
Order By: Relevance
“…These findings contrast with the conclusions of a recent publication, which reported that nitric oxide donors promote an increase in AMPK phosphorylation (38). The conclusions of this previous paper were largely based on experiments in which treatment of cultured cells with pharmacological NO donors, such as SNP, increased AMPK phosphorylation in HeLa cells and in human umbilical vein endothelial cells.…”
Section: Discussioncontrasting
confidence: 56%
“…These findings contrast with the conclusions of a recent publication, which reported that nitric oxide donors promote an increase in AMPK phosphorylation (38). The conclusions of this previous paper were largely based on experiments in which treatment of cultured cells with pharmacological NO donors, such as SNP, increased AMPK phosphorylation in HeLa cells and in human umbilical vein endothelial cells.…”
Section: Discussioncontrasting
confidence: 56%
“…These findings, which suggest that the regulation of Akt phosphorylation in response to nitric oxide is independent of mTOR, are consistent with previous reports showing that Akt is a direct target for inhibitory S-nitrosation by nitric oxide (58). Overall, these findings confirm that nitric oxide activates AMPK (2,34,61) and that AMPK activation correlates with Raptor phosphorylation and the inhibition of mTORC1 signaling (13). These studies also suggest that nitric oxide may alter mTOR signaling in part through AMPK activation.…”
Section: Nitricsupporting
confidence: 81%
“…While nitric oxide stimulates cellular damage, it also activates a number of signaling pathways that limit additional cellular damage and repair existing damage. In pancreatic ␤-cells, the protective responses activated by nitric oxide include (i) JNK-dependent induction of GADD45␣ (growth arrest and DNA damage-inducible protein 45␣) and DNA repair, (ii) activation of AMP-activated protein kinase (AMPK), resulting in enhanced metabolic recovery, and (iii) activation of the unfolded-protein response (UPR) (25,34,38,54,57,61).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, AMPK is also activated during ischemic preconditioning (40,41), the physiologic phenomenon by which preceding short durations of ischemia decrease the susceptibility to necrosis during more prolonged and potentially injurious ischemia. AMPK is also activated by other treatment regimens that prevent ischemic injury, such as heat shock (10), adrenergic stimulation (42), and nitric oxide (43). AMPK activation is sufficient to precondition the heart, based the results of recent pharmacologic studies with a direct AMPK activator (41).…”
Section: Discussionmentioning
confidence: 99%